Graphene functionalized carbon felt/graphite felt fabrication as electrodes for vanadium redox flow batteries (VRBs): A review - Teo, Ellie Yi Lih; Omar Faruqi, Marzuki; Chong, Kwok Feng (Universiti Putra Malaysia Press, 2023)
The growth in the development of renewable energy sources has led to tremendous attention to the research in energy storage systems. One of the electrochemical energy storage systems that have shown great potential to be used on a large scale is vanadium redox flow batteries (VRBs), as they possess flexible designs, long life cycles, and high energy density. Carbon felts (CF), and graphite felts (GF) have commonly been used as electrodes in VRBs. To improve market penetration using VRB technology, researchers have focused on electrode modifications to increase the power density and rate capabilities of VRBs. One of the carbon-based modifications which have shown significant improvements in the performance of VRBs is the use of graphene, which has outstanding electrochemical and physical characteristics as an electrocatalyst. In this review, electrochemical, physical, and other methods which have been reported in the graphene functionalization of graphite felt/carbon felt are discussed. The working principle and limiting methods were elaborated on and discussed for each method. Finally, recommendations for future developments are also highlighted.